Iron-deficiency anaemia in calves and lambs. (2nd January 2023) - Plate, Peter
Abstract : While iron-deficiency anaemia is well recognised in piglets, the importance of its diagnosis and treatment in calves and lambs has been highlighted more recently. In particular, housed lambs and calves fed on whole milk are prone to subclinical iron deficiency anaemia, with surveys showing prevalence figures from 20% to more than 50%. Many studies show reduced daily liveweight gain as a main clinical sign in both species; some also show health issues such as increased risk of pneumonia and diarrhoea in calves and an increase in abomasal bloat risk in lambs. Iron supplementation trials consistently led to higher growth rates pre-weaning and to improved haematological values. In the UK, there are no injectable iron preparations licensed for calves or lambs, but preparations licensed for pigs can be used off label.